The DC electrical Conductivity of prepared pure polypyrrole and polypyrrole /graphene (PPY/GN) nanocomposite by in-situ polymerization - Ahmed, fatima mikdad; Hassan, Salma Mohammad; Kamil, Mohanad Irzooqi (Iraqi Journal of Physics, 2020)
Abstract In this work, pure Polypyrrole (PPy) and Polypyrrole (PPy)/Graphene (GN) was synthesized by in-situ polymerization in different weight percentages (0.1, 0.3, 0.5, 1, 3 and 5 wt.% (g)) of GN nano particles using chemical oxidation method at room temperature. The FTIR, SEM and electrical properties were studies for the nano composites. The result show that when concentration of GN Nano particle increase, the electrical conductivity increased and the graphene sheets were merging to form a continuous area of the GN through the polypyrrole base material. The FTIR spectra shows that the characteristics absorption peaks of polypyrrole that is, 1546.80, 1463.87 and 3400.27 cm-1(stretching vibration in the pyrrole ring), and at 1080.06 cm-1 was assigned to C—O stretching and at 1589.23 cm-1 was assigned to C—C vibration of carbon ring in graphene. الخلاصة حضر البولي بايرول النقي و المطعم بدرجة حرارة الغرفه بطريقة الاكسدة الكيميائية و قد تم استخدام جسيمات الكرافين النانوية و بالنسب التالية (0.1, 0.3, 0.5, 1. 3, ,5 %). و تم استخدام طيف الاشعه تحت الحمراء و ماسح الالكترون المجهري لتشخيص البولي بايرول المحضر كما قيست التوصيلية الكهربائية المستمرة و اوجدت النتائج ان التوصيلية تزداد بزيادة درجه الحرارة و كذالك بزيادة الكرافين .